Attitudes among Geography Teachers in Bosnia and Herzegovina toward Geospatial Technology Use: Gender, Age and Regional Differences - Avdić, Boris; Drešković, Nusret; Mirić, Ranko (Geographica Pannonica, 2020)
The use of geospatial technology at lower levels of education has become a global tendency. However, Bosnia and Herzegovina is a country that is virtually uncharted in this regard, and the present paper has the main purpose to change that fact. Results of a survey conducted among geography teachers place this country within the entry category. Different attitudes among various groups of teachers (based on gender, age and regional distribution) have also been tested. Although the general hypotheses could not be confirmed, certain specific differences have been found, such as in the use of virtual globes, theoretical knowledge of GIS and willingness to attend educational training courses.